Impact of Virtual Physics Laboratory on Students’ Academic Achievement in Physics - Babalola , F. E.; Alabi, D. O. (Kashere Journal of Education, 2021)
Practical science learning activities are relevant to both the acquisition of skills and the understanding of concepts. Unfortunately, there are considerable challenges in providing effective and efficient teaching of practical science. In most science classrooms across the economically developed countries, science learning has been supported and enabled for many years by a range of technologies that supplement traditional pedagogical approaches. However, the use of ICT in physics education in Africa’s schools has been patchy and limited. This study examined the effectiveness of virtual physics laboratories on student understanding of physics concepts within an African context.120 secondary school students from two schools in south-western Nigeria were divided into experimental and control groups who carried out virtual and physical experimental activities respectively. Pre- and post-tests of conceptual understanding were administered to the groups and the results were analyzed using t-tests. Two hypotheses on the relative value of the two forms of learning activity and the relative performance of boys and girls were tested. The data showed that students that were engaged through the virtual physics laboratory performed better than students taught in the traditional physics laboratory. In the experimental group boys benefited more than girls from the virtual physics laboratory activities. Although these data are limited in scope they suggest that virtual laboratories could help in overcoming the challenges faced in the provision of traditional laboratories.